Anterior sagittal anorectoplasty: Our experience - Ram Babu Goyal; Rahul Gupta; Girish Prabhakar; Monika Bawa (Wolters Kluwer Medknow Publications, 2020)
Context: Anterior sagittal anorectoplasty (ASARP) is accepted as one of the techniques for the repair of vestibular fistula (VF) and low-type anomalies, but some may have reservations. Aims: The aim of the study is to describe the technique, important features, and functional and cosmetic outcomes of ASARP for the treatment of anorectal malformation (ARM) in females. Settings and Design: A prospective study was performed from 1992 to 2017. Materials and Methods: The study included 157 pediatric patients (aged 1-15 years) with diagnosis of ARMs with VF, perineal fistula (perineal ectopic anus), and rectovaginal fistula managed by ASARP. Results: Most cases (36.94%) were 1-6 months' age group; 92.99% of patients (146) were having VF, 5.09% (8) perineal fistula, and 1.91% (3) rectovaginal fistula. Associated anomalies (37) were present in 19.75% (31) of patients. Primary ASARP was performed in 85.35% (134) of cases. The mean operative time was 105 (±15) min. Intraoperative complications were seen in 3.82% (6) of patients. Early postoperative complications were seen in 5.09% (8) of patients - wound infection (4), wound dehiscence (3), and retraction of the rectum (1). Late complications were seen in 12.73% (20) of cases. Overall, five patients developed anal stenosis, two responded to dilatation therapy, and three required anoplasty. The external appearance of the perineum after the 3rd month (postoperatively) was satisfactory in 95.54% (150); overall, 4.46% (7) of patients required the second procedure. Stooling pattern could be assessed in 80.25% (126) of patients at 3 years' age group. Only one had poor outcome with severe soiling (incontinence) and perineal excoriation that also had myelomeningocele. Conclusions: ASARP is an excellent procedure for VF as it results in optimal correction with minimal sphincteric damage, without additional complexity or difficulties. Primary ASARP is a quick and effective technique and does not require colostomy if performed after due preoperative gut preparation and by an experienced pediatric surgeon.